Assembly stoichiometry of bacterial selenocysteine synthase and SelC (tRNAsec). Issue 7 (18th February 2013) - Manzine, Livia Regina; Serrão, Vitor Hugo Balasco; Lima, Luis Maurício Trambaioli da Rocha e; de Souza, Marcos Michel; Bettini, Jefferson; Portugal, Rodrigo Villares; van Heel, Marin; Thiemann, Otavio Henrique
Abstract : In bacteria selenocysteyl–tRNA sec (SelC) is synthesized by selenocysteine synthase (SelA). Here we show by fluorescence anisotropy binding assays and electron microscopical symmetry analysis that the SelA–tRNA sec binding stoichiometry is of one tRNA sec molecule per SelA monomer (1:1) rather than the 1:2 value proposed previously. Negative stain transmission electron microscopy revealed a D5 pointgroup symmetry for the SelA–tRNA sec assembly both with and without tRNA sec bound. Furthermore, SelA can associate forming a supramolecular complex of stacked decamer rings, which does not occur in the presence of tRNA sec . We discuss the structure–function relationships of these assemblies and their regulatory role in bacterial selenocysteyl–tRNA sec synthesis. Abstract : ► SelA–tRNA sec binding stoichiometry of five tRNA sec per SelA decamer is incorrect. ► Direct and reverse fluorescence anisotropy show a stoichiometry of one 1:1. ► EM symmetry analysis shows a D5 pointgroup symmetry for the SelA–tRNA sec complex. ► The correct stoichiometric ratio of 1:1 SelA–tRNA sec is revealed.